Detallar la variación de las importaciones de carga general en el puerto de santa marta: 2017 al 2021. una mirada a este tipo de carga. (2024)
Imports play a crucial role in an international logistics chain, as they enable companies to source products and raw materials from other countries to meet market demand, involving the planning and coordination of various logistics activities, such as international transportation, customs management, warehousing, and distribution. In addition, imports contribute to economic growth, generating employment and promoting global competitiveness. In the following study, a contextualization of the state of imports and port operations of the port of Santa Marta against general cargo type goods in the periods 2017 - 2021 was carried out. It analyzed the trends of general cargo, identified the main imported products, and a SWOT analysis was performed. The methodology applied in this research is descriptive analytical type with a deductive method that begins with the description, analysis and evaluation of data collected in order to obtain information directly related to our topic of study. The collection and review of relevant material includes (secondary) information on the geographic characteristics of the port of Santa Marta, its infrastructure, and available logistic resources, and thus the results obtained provide valuable information for strategic decision making and the development of commercial policies in the port.